2018
DOI: 10.3389/fendo.2018.00573
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-tumoral Properties of Orexin/Hypocretin Hypothalamic Neuropeptides: An Unexpected Therapeutic Role

Abstract: Orexins (OxA and OxB) also termed hypocretins are hypothalamic neuropeptides involved in central nervous system (CNS) to control the sleep/wake process which is mediated by two G protein-coupled receptor subtypes, OX1R, and OX2R. Beside these central effects, orexins also play a role in various peripheral organs such as the intestine, pancreas, adrenal glands, kidney, adipose tissue and reproductive tract.In the past few years, an unexpected anti-tumoral role of orexins mediated by a new signaling pathway invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 104 publications
1
35
0
Order By: Relevance
“…Studies have shown that the Gi pathway [22,23] and Gq pathway [24][25][26] are involved in the action of OXA, and other signaling pathways such as cAMP, MAPK-ERK 1/2 , PI3K/Akt, and JNK are also involved [25]. Further studies have confirmed that OXA plays a protective role in diseases and pathophysiological processes through…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Studies have shown that the Gi pathway [22,23] and Gq pathway [24][25][26] are involved in the action of OXA, and other signaling pathways such as cAMP, MAPK-ERK 1/2 , PI3K/Akt, and JNK are also involved [25]. Further studies have confirmed that OXA plays a protective role in diseases and pathophysiological processes through…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…In 2011, our group had demonstrated that OX1R but not OX2R was highly expressed in colon cancer cell lines and colorectal tumors from patients (139). It should be noted that: (1) no detection of prepro-orexin was observed in normal and tumoral colonic epithelia (139) and (2) OX1R was not detected in normal colon epithelium (22). Orexins treatment of digestive cancer cell lines derived from colon, pancreas and liver cancers (22, 139, 143) induced a strong cell death by apoptosis.…”
Section: Orexins In Diseasementioning
confidence: 99%
“…It should be noted that: (1) no detection of prepro-orexin was observed in normal and tumoral colonic epithelia (139) and (2) OX1R was not detected in normal colon epithelium (22). Orexins treatment of digestive cancer cell lines derived from colon, pancreas and liver cancers (22, 139, 143) induced a strong cell death by apoptosis. The orexin-induced apoptosis was mediated by the phosphorylation of two tyrosine-based motifs (ITIM) present in the receptor sequence.…”
Section: Orexins In Diseasementioning
confidence: 99%
See 2 more Smart Citations